Sphingolipids and expression regulation of genes in cancer - Patwardhan, Gauri A. (2010)
Sphingolipids including glycosphingolipids have myriad effects on cell functions and affect cancer in aspects of tumorigenesis, metastasis and tumor response to treatments. Bioactive ones like ceramide, sphingosine 1-phosphate and globotriaosylceramide initiate and process cellular signaling to alter cell behaviors immediately responding to oncogenic stress or treatment challenges. Recent studies pinpoint that sphingolipid-mediated gene expression has long and profound impacts on cancer cells, and these play crucial roles in tumor progression and treatment outcome. More than ten sphingolipids and glycosphingolipids selectively mediate expressions of approximate fifty genes including c-myc, p21, c-fos, telomerase reverse transcriptase, caspase-9, Bcl-x, cyclooxygenase-2, matrix metalloproteinases, integrins, Oct-4, glucosylceramide synthase and multidrug-resistant gene 1. By diverse functions of these genes, sphingolipids enduringly affect cellular processes of mitosis, apoptosis, migration, stemness of cancer stem cells and cellular resistance to therapies. Mechanistic studies indicate that sphingolipids regulate particular gene expression by modulating phosphorylation and acetylation of proteins that serve as transcription factors (β-catenin, Sp1), repressor of transcription (histone H3), and regulators (SRp30a) in RNA splicing. Disclosing molecular mechanisms by which sphingolipids selectively regulate particular gene expression, instead of other relevant ones, requires understanding of the exact roles of individual lipid instead of a group, the signaling pathways that are implicated in and interaction with proteins or other lipids in details. These studies not only expand our knowledge of sphingolipids, but can also suggest novel targets for cancer treatments.